1999
DOI: 10.3354/dao038067
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase chain reaction (PCR) detection of white spot syndrome virus (WSSV) in cultured and wild crustaceans in India

Abstract: A study was carried out to evaluate polymerase chain reaction (PCR) for the detection of white spot syndrome virus (WSSV) in postlarvae and broodstock of Penaeus monodon and in potential crustacean carriers from India. Primer pairs designed for WSSV affecting Penaeus japonicus (WSSV PJ) and P. monodon (WSSV PM) were used. Both the primer pairs gave positive assay results for crustaceans showing gross signs of WSSV infection. However, all grossly healthy postlarvae and broodstock gave negative results with both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 11 publications
2
56
3
1
Order By: Relevance
“…Within a short span of time, the disease became pandemic and the farmers suffered severe loss as most of the farms were virtually wiped out because of this. Shrimp aquaculture in India too suffered significantly due to WSSV infection [9,22]. Subsequently, several attempts made by the farmers faced repeated failures and they continued to bear the loss.…”
Section: Introductionmentioning
confidence: 99%
“…Within a short span of time, the disease became pandemic and the farmers suffered severe loss as most of the farms were virtually wiped out because of this. Shrimp aquaculture in India too suffered significantly due to WSSV infection [9,22]. Subsequently, several attempts made by the farmers faced repeated failures and they continued to bear the loss.…”
Section: Introductionmentioning
confidence: 99%
“…Mud crab has been shown to be a carrier of WSSV in Taiwan and Thailand , Supamattaya et al, 1998. Otta et al (1999) have tested one mud crab with external symptoms and 20 healthy samples without white spots and reported that the one with external symptoms is positive in the 1 st step PCR whereas 3 out of 20 healthy specimens are positive in the 2 nd step PCR indicating that S. serrata is also a carrier of WSSV. In India, it has been noticed that the natural prevalence of WSSV in crab is about 5.06% while in shrimp culture ponds it is about 30% (CIBA, 2009).…”
Section: Discussion:-mentioning
confidence: 99%
“…Kou et al (1998) have opined that the sensitivity of the 2-step amplification is 10 3 to 10 4 times greater than that of the 1-step amplification. Otta et al (1999) have carried out a study to evaluate the crustaceans as potential carriers of WSSV using PCR. After the WSSV outbreaks in India during late 1994, in the shrimp culture ponds, several instances of White spots on the exoskeleton of mud crab, S. serrata have been observed.…”
Section: Discussion:-mentioning
confidence: 99%
“…In shrimp farms from India, (Otta et al, (1999) and Vaseeharan and Ramasamy (2003) noted that vibrio species accounted for 38-81% of the bacterial biota. In this study, the edible sea food samples analysed were found to contain Staphylococcus spp, Enterobactericeae spp and vibrio species of which Vibrio parahaemolyticus is an organism of concern not only because some strains of this species were associated with diseases in sea foods but also because some strains of this species are human pathogens, causing gasteroenteritis (Saqkazaki et al, 1968;Honda et al, 1987;Farmer and Hickman-Brenner, 1992;Powell, 1999).…”
Section: Fig5 Vibrio Parahaemolyticus In Tcbs Agarmentioning
confidence: 99%